Organizational contexts, team designs and process variables: factors contributing to team effectiveness / Kay Dora Abd Ghani, Mohammad Ismail and Mohd Subri Tahir - Abd Ghani, Kay Dora; Ismail, Mohammad; Tahir, Mohd Subri (2008)
Much has been said and written about the importance of teams to the success of organizations and emphasis has been given to the benefits of team-building activities in achieving both team and organizational effectiveness. A lot of research describes attempts to move beyond team building and to' link organizational development to team effectiveness in a coherent way. There is vast literature which addresses the topic on team effectiveness. The purpose of this paper is to investigate the team effectiveness factors which focus on the organizational contexts, team design and process variable within a manufacturing company involved in a cement industry. The results indicate that these three independent variables are major contributors to team effectiveness.